La protección de los niños, niñas y adolescentes ante la alineación parental a partir del código de la niñez y la adolescencia - Mafla, Britney J. (2023)
In the midst of the clamor for human rights, the most vulnerable and delicate voices in our society have often been relegated: children and adolescents. However, in recent decades, a tireless movement has gained momentum, demanding the recognition and respect of the fundamental rights that belong to them from the moment of birth, which is why this research aimed to analyze the protection measures in force in the Ecuadorian legal system against parental alienation as a type of violence against the rights of children and adolescents; It was founded around the following question: Are the protection measures in force in the Ecuadorian legal system adequate to protect the rights of children and adolescents against parental alienation as a type of violence? since every right must contain a protection mechanism for its correct execution; The present work was carried out around a qualitative and analytical, descriptive approach and research techniques such as documentary review, guide and observation sheet, in order to obtain the following result, that the figure of parental alienation is not singled out in the regulations Ecuadorian law, which has made its timely detection impossible, but it does contain certain protection measures that may be applicable in such cases, so that there is a correct execution of rights, a result obtained after an exhaustive analysis, including from a comparative perception with other legislations that He is already working on the issue of parental alienation.